Partial weight reduction protocols in cats lead to better weight outcomes, compared with complete protocols, in cats with obesity - German, Alexander J.; Woods-Lee, Georgiana R. T.; Biourge, Vincent; Flanagan, John (Frontiers in Veterinary Science, 2023)
Background: To date, there have been no studies comparing outcomes of cats with obesity following either complete or partial weight reduction protocols. Methods: Fifty-eight cats participated in this non-randomized observational cohort study, including 46 (79%) and 12 (21%) that underwent complete or partial weight reduction protocols, respectively. Weight loss outcomes, body composition changes and essential nutrient intake were compared between cats in the two groups. Results: All cats remained healthy, and those on a complete weight reduction protocol lost a median of 23% (range 10-39%) of starting body weight (SBW) over 294 days (113-967 days), whereas those undergoing partial restriction lost 25% (10-41%) over 178 days (54-512 days). Neither duration nor percentage weight loss differed between groups, but those that followed a partial weight reduction protocol lost weight at a faster rate (0.81% per week) and required fewer visits (7, 4-19) than those that followed a complete weight reduction protocol (0.61% per week, P=0.028; 11, 4-40 visits, P=0.009). Further, lean tissue mass declined in cats on a complete weight reduction protocol (pre: 4.20 kg, 2.64-5.72 kg; post: 3.90 kg, 2.76-5.24 kg, P<0.001), whereas lean tissue mass was unchanged in cats on partial weight reduction protocols (pre: 3.45 kg, 2.79-4.71 kg; post: 3.41 kg, 2.90-4.59 kg, P=0.109). In 33 (57%) cats, median intake of selenium per day was less than NRC AI and RA recommendations, whilst intake was under FEDIAF recommendation in 42 (72%) cats. Median intake of choline per day was less than NRC MR and RA recommendations in 22 (38%) and 53 (91%) cats, respectively, whereas it was under the FEDIAF recommendation in 51 (88%) cats. In a small proportion (12-14%) of cats, phenylalanine/tyrosine and potassium were under recommendations; besides these, no other essential nutrient deficiencies were seen, and there were no differences between cats undergoing complete and partial weight reduction. Conclusion: Partial weight reduction protocols in cats lead to quicker average weight loss, with the possibility that lean tissue loss might be minimized. Such protocols might be more suitable for older cats and those with marked obesity.